2006
DOI: 10.1007/s10653-006-9050-4
|View full text |Cite
|
Sign up to set email alerts
|

A Screening-Level Assessment of Lead, Cadmium, and Zinc in Fish and Crayfish from Northeastern Oklahoma, USA

Abstract: The objective of this study was to evaluate potential human and ecological risks associated with metals in fish and crayfish from mining in the Tri-States Mining District (TSMD). Crayfish (Orconectes spp.) and fish of six frequently consumed species (common carp, Cyprinus carpio; channel catfish, Ictalurus punctatus; flathead catfish, Pylodictis olivaris; largemouth bass, Micropterus salmoides; spotted bass, M. punctulatus; and white crappie, Pomoxis annularis) were collected in 2001-2002 from the Oklahoma wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
2
42
2
Order By: Relevance
“…Among the heavy metals analyzed in Langat River and Cempaka lake Malaysia, Cr had the HQ value greater than 1 for culture pond A and culture pond B, Langat River. While the HQ value for Pb ranged from 0.017 to 0.073 which were much lower than those measured in Tri states mining districts where the HQ ranged from 0.1 to 4.6 (Schmitt et al, 2006). In the study at Langat River and Cempaka Lake, Malaysia, although the observed values of HQ for Pb, Cd, Ni, Cu and Zn were lower than the safe standard of 1, but ΣHQ of these metals (HI) were higher t han 1.…”
Section: Analysis Of Exposures In Samplescontrasting
confidence: 61%
See 1 more Smart Citation
“…Among the heavy metals analyzed in Langat River and Cempaka lake Malaysia, Cr had the HQ value greater than 1 for culture pond A and culture pond B, Langat River. While the HQ value for Pb ranged from 0.017 to 0.073 which were much lower than those measured in Tri states mining districts where the HQ ranged from 0.1 to 4.6 (Schmitt et al, 2006). In the study at Langat River and Cempaka Lake, Malaysia, although the observed values of HQ for Pb, Cd, Ni, Cu and Zn were lower than the safe standard of 1, but ΣHQ of these metals (HI) were higher t han 1.…”
Section: Analysis Of Exposures In Samplescontrasting
confidence: 61%
“…Similar to the findings, Tu et al (2008) worked on the concentration of Cr, Cu, Zn and Cd, and measured HQ values of less than 1 which indicated that the local residents were not exposed to potential risk via consumption of shrimp. On the other hand, Schmitt et al (2006) reported a higher range of HQ values for Cd (0.1 to 0.5) and Zn (0.1 to 12.6) in carp fishes. Samples of black-chin Tilapia, collected from Sukumo lagoon of Ghana, were analyzed for the concentration of heavy metals and the calculated values of HI indicated that the Tilapia did not pose any health risk to humans (Laar et al, 2011).…”
Section: Analysis Of Exposures In Samplesmentioning
confidence: 84%
“…Nonetheless, urine cadmium concentrations in the SHS participants were higher than in the general US population. 41 Although the prevalence of smoking is higher in American Indians than in other US ethnic groups, [42][43][44] their intensity of smoking is markedly lower, 43 and sources of exposure other than smoking, such as occupational and environmental exposures, 40,[45][46][47] may be involved in the increased urine cadmium concentrations in our study population.…”
Section: Discussionmentioning
confidence: 87%
“…However, elemental contaminants also are natural constituents of the earth's crust; some are essential trace elements for terrestrial and aquatic organisms. In spite of regulation, elemental concentrations in fish remain elevated in some areas due to irrigated agriculture (Hamilton 2004), mining (Schmitt et al 2006), and the combustion of fossil fuels (Baumann and Gillespie 1986;Yeardley et al 1998), and both organochlorine and elemental contaminants are distributed globally by atmospheric transport. Considered independently, concentrations of most organochlorine residues and elemental contaminants we evaluated represented no or low risk to bald eagle and mink.…”
Section: Discussionmentioning
confidence: 99%